MAKING E-COMMERCE ON THE WEB BUANA TOURS & TRAVEL THROUGH THE USE OF ACTIVE SERVER PAGES - Fitrahny Saru; Eko Hadiyanto, SSi, MMSI Eko Hadiyanto, SSi, MMSI (Jurnal Sistem Informasi, 2002)
Trade via internet, or better known by the term e-commerce, lately been increasinglyrife with bermunculnya companies offering goods and services on the web site online.Therefore, the author will discuss about creating a web-based server by using ActiveServer Pages (ASP) at a travel agency Buana Tours & Travel. ASP allows developersto work on the process server.